Keeping the Faith: Filipino Catholic Responses to the Covid-19 Pandemic - Nestor T. Castro (International Journal of Interreligious and Intercultural Studies, 2022)
Since March 2020, Metro Manila and other places in the Philippines has been on lockdownbecause of the surge of Covid-19 cases in the country. Even churches and other places ofworship have been off-limits to church goers during strict lockdown measures called “EnhancedCommunity Quarantine.” This paper looks at how Filipino Catholics practice their religiousobligations during the pandemic. Since majority (81%) of Filipinos are Roman Catholics, thefocus of this paper is how Filipino Catholics view the Covid-19 pandemic and how they copewith it. The data for this study comes from two sources: 1) interviews with church leaders andlay members; and 2) online and offlne ethnographic observation of religious practices duringthe pandemic. Through an anthropological description of Filipino Catholic attitudes on andresponses to the Covid-19 pandemic, we have a better understanding about Filipino resiliencyin times of crises.